Analysis of cutaneous allergic reactions in clinical trials of eslicarbazepine acetate. (23rd January 2020) - Rogin, Joanne; Resnick, Trevor; Strom, Laura; Ben‐Menachem, Elinor; Kochen, Silvia; Blum, David; Gama, Helena; Soares‐da‐Silva, Patrício; Li, Yan; Grinnell, Todd
Abstract : Objectives: To evaluate cutaneous allergic reactions in clinical trials of adjunctive eslicarbazepine acetate (ESL) for focal seizures. Materials and methods: Data were analyzed from three phase III randomized, double‐blind, placebo‐controlled studies of adjunctive ESL in adults (placebo, n = 426; ESL, n = 1021) and two randomized, double‐blind, placebo‐controlled studies (and open‐label extensions [OLEs]) of adjunctive ESL in children aged 4‐17 years (placebo, n = 160; ESL, n = 202; OLE, n = 337). Results: Adult studies : Rash (ESL 1.9%, placebo 0.9%) and pruritus (ESL 1.2%, placebo 0.9%) were the most frequent rash‐related treatment‐emergent adverse events (TEAEs). Most rash‐related TEAEs were mild or moderate in severity. Incidence of rash increased with increasing ESL dose, but was not higher for patients who initiated treatment with higher ESL doses. Pediatric studies : Allergic dermatitis (ESL 3.0%, placebo 0) and rash (controlled studies: ESL 1.0%, placebo 1.3%; OLE periods: ESL ≤1.2%) were the most frequent rash‐related TEAEs. There was one case of DRESS in the ESL group. Most rash‐related TEAEs were mild or moderate in severity and judged as not related to treatment with ESL. Conclusions: Serious skin rashes were rare during adult and pediatric clinical trials of ESL. Although the incidence of rash with ESL was low, it is important for patients/caregivers to be made aware of the potential signs and symptoms associated with serious skin rashes.